An introduction to policing - Dempsey, John S.; Forst, Linda S. (Australia ; Clifton Park, NY : Delmar Cengage Learning, 2009)
This book is about Law enforcement, American policing, organizing puplic and private security in the United States. Including the personal side of policing, police operation, critical issues in policing, technology and homeland security.
Part I : Police history and organization. Police hsitory -- Organizing public and private security in the United States -- Organizing the police department -- Part II : The personal side of policing. Becoming a police officer -- The police role and police discretion -- Police culture, personality, and police stress -- Minorities in policing -- Police ethics and police deviance -- Part III : Police operations. Patrol operations -- Investigations -- Police and the community -- Community policing : the debate continues -- Police and the law -- Part IV : Critical issues in policing. Computers, technology, and criminalistics in policing -- Homeland security.
Includes bibliographical references (pages 567-577) and index.
Keywords: Law enforcement -- United States; Police -- United States